Complicaciones asociadas con osteotomía Le Fort I Complications associated with Le Fort I osteotomy - Francisco L Duque S; Pedro M Jaramillo V (Universidad de Antioquia, 2009)
La osteotomía Le Fort I es un procedimiento rutinario en cirugía ortognática. Los autores reportan la ocurrencia de complicaciones intra- y posquirúrgicas. La osteotomía Le Fort I está relacionada con gran variedad de complicaciones. Un conocimiento preciso de las complicaciones debería ayudar al cirujano, al ortodoncista y al paciente para estimar los beneficios de una cirugía electiva versus los riesgos. El conocer las complicaciones también debería ayudar a prevenir su ocurrencia y facilitar el tratamiento. El propósito de esta revisión fue reportar las complicaciones quirúrgicas y posquirúrgicas que están relacionadas con la osteotomía Le Fort I. Se presentan las complicaciones en el siguiente orden: oftalmológicas, vasculares, del seno cavernoso, necrosis avascular, edema, infecciosas, neurológicas, resultados estéticos desfavorables, cambios pulpares y otras complicaciones de rara ocurrencia. Le Fort I osteotomy has become a routine procedure in elective orthognathic surgery. The authors report the occurrence of intra and post operative complications in Le Fort I osteotomy. The Le Fort I osteotomy is related to a variety of complications. A precise assessment of complications might be helpful for the patient, the orthodontist, and the surgeon in order to estimate the benefit of an elective operation versus its immanent risks. Knowledge of complications also might help to prevent their occurrence and facilitate their management. The aim of this review was to report the types and frequencies of intra- and post operative complications related to Le Fort I osteotomy. This review presents surgical complications in the following order: Ophthalmic complications, Vascular complications, Cavernous sinus fistula, Ischemic complications including aseptic necrosis, swelling, significant infections such as abscesses or maxillary sinusitis, Nerve injures, unfavorable esthetic results, unfavorable pulpal reactions and other unusual complications.